Analisis Perputaran Piutang pada Ultra Jaya Milk Industry & Trading Company Tbk yang Terdaftar di Bursa Efek Indonesia - Susanti (LANCAH: Jurnal Inovasi dan Tren, 2024)
This research aims to analyze the turnover of receivables in food and beverage companies listed on the Indonesia Stock Exchange (BEI) during the period 2020 to 2023. The data used in this research comes from 2020 to 2023 which is available on the IDX. Data analysis uses quantitative descriptive methods to measure the level of accounts receivable turnover. The company sampled in this research is Ultra Jaya Milk Industry & Trading Company Tbk, using financial reports, namely balance sheets and profit and loss reports for the 2020-2023 period. The research results show that in 2020, Ultra Jaya Milk Industry & Trading Company Tbk had low receivables collection performance, with a receivables turnover ratio of 4 times. In 2021, receivables collection performance will improve to ideal, with a receivables turnover ratio of 15 times. In 2022, the company demonstrated excellent receivables collection performance, with a receivables turnover ratio reaching 18 times, and in 2023, receivables collection performance remained high, even though the receivables turnover ratio fell to 7 times.